Association between obesity and Bell’s palsy by combining Mendelian randomization and network pharmacology - Li Zhong; Wei Jiang; Liu Yan; Juan Huang (2025)
The issue of obesity has emerged as a significant global health challenge; nevertheless, the association between Bell's palsy (BP) and obesity remains ambiguous. In this study, the Mendelian randomization (MR) approach was employed to investigate their relationship, while network pharmacology methods were utilized to unveil the underlying mechanisms. We utilized single nucleotide polymorphisms closely linked to obesity and BP as instrumental variables for the MR analysis. Four robust bidirectional MR analysis methods, namely inverse variance weighting (IVW), weighted median, weighted mode, and MR-Egger were employed to assess the association between obesity and BP. Additionally, sensitivity analysis was conducted to evaluate levels of heterogeneity, sensitivity, and stability. Furthermore, we identified therapeutic targets associated with obesity and BP. Subsequently, a protein-protein interaction network analysis was conducted. Finally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were employed to investigate potential mechanisms underlying the relationship between obesity and BP. The IVW analysis demonstrated a significant positive correlation between obesity and BP (odds ratio [OR] = 1.267, 95% confidence interval [95% CI] = 1.049-1.530, P = .013). However, there was no evidence to suggest that BP increased the risk of obesity. Furthermore, network pharmacology analysis revealed that the 2 diseases shared a total of 712 common targets. GO enrichment analysis shows that this process mainly regulates chemical synaptic signal transmission by modulating receptor signaling factor activity, receptor ligand activity, etc. KEGG enrichment analysis shows that the EGFR/PI3K/Akt signaling pathway plays a significant role in this process. Our study findings suggest that obesity may increase the risk of BP, and its underlying mechanism may potentially involve regulating chemical synaptic transmission through the EFGR/PI3K/Akt signaling pathway.